DEVELOPMENTAL FEATURES OF CHILDREN’S SPEECH OF EARLY AGE - Meliboyev Tavakkaljon Turgunovich (Galaxy International Interdisciplinary Research Journal, 2024)
The article provides information on the characteristics of children’s speech development, the need for a correct diagnosis of speech disorders, the characteristic of a child with normal speech development, mispronunciation of certain sounds at a young age.